Efficient language teaching software in a multimedia context - Nagy, László T.; Stóka, Ágnes (Teaching Mathematics and Computer Science, 2012)
In this article I deal with the efficiency of multimedia teaching programs, analyzing possibilities for their improvement in the field of language teaching. This research has been carried out with the use of the latest technologies, language teaching software, internet based language teaching applications, digital dictionaries, online content, and the latest results from the field of computational linguistics. The goal of my research is to create a general model that serves and supports various kinds of approaches to improving efficiency; I cannot attempt to present a complete, detailed analytical review due to the complexity and size of this topic. However, my opinion is that by considering and understanding the theoretical aspects of the subject, and supported by certain important ideas, we will be able to achieve remarkable improvements in the field of learning efficiency and knowledge retention in the language teaching and learning process that might lead to outstanding results.